Conidiobolomycosis in sheep in the state of pernambuco - Mendonça, Fábio Souza; Albuquerque, Raquel Feitosa; Evêncio-Neto, Joaquim; Dória, Renata Gebara Sampaio; De Camargo, Lázaro Manoel [UNESP]; De Freitas, Silvio Henrique [UNESP] (My University, 2012)
An outbreak of zigomycosis with rhinopharyngeal lesions involving fungal hyphae with characteristic of entomophthoromycosis due to Conidiobolus spp. is reported in the State of Pernambuco, Northeastern Brazil. The epidemiological, clinical, pathological and mycological findings are decrypted in a flock of Santa Inês sheep. The disease occurred at Nazaré da Mata from April to May 2009, all most cases occurred mainly during the rainy season affecting 5 sheep of 29, resulting in death of about 100% of the affected sheep. Clinical signs as noisy respiration and dyspnoea due to mechanical blockage of the nasal cavities, swelling of the nostrils and mucous or serosanguineousnasal discharge were observed. Two of 5 sheep showed exophthalmia, keratitis and unilateral corneal ulceration of the eye. The sheep either died of their infection or were euthanized after a clinical course of 7-20 days. At necropsy there was a firm whitish, lobulated, friable growth was evident in the ethmoidal region and nasal septum at the sagital sections of the head from four affected sheep. Histopathologically findings were multifocal granulomas with lymphocytic infiltration, epithelioid multinucleated giant cells and fibrovascular tissue, surrounding an eosinophilic necrotic reaction (Splendore-Hoeppli phenomenon). The methenamine-silver stain uncovered fungal hyphae, rarely ramified with bulbous dilatation in their extremities. Conidiobolus sp. was isolated from nasal tissue lesions of two sheep. This is the first report of disease in the State.
Conidiobolomicose em ovinos no estado de pernambuco
Keywords: Entomophthoromycosis; Sheep; Zygomicetes